Pengaruh Intensitas Cahaya Terhadap Nyala Lampu dengan Menggunakan Sensor Cahaya Light Dependent Resistor - Nurhayati Nurhayati; Besty Maisura (CIRCUIT: Jurnal Ilmiah Pendidikan Teknik Elektro, 2021)
The purpose of this research is to analyze the relationship between the intensity of light hitting the LDR to the resistance and the flame of the light. The research created an automatic lighting system, in which the lighting system was designed to turn on or off lights by light intensity. This research created automatic light controls using LDR light sensor. The LDR light sensor set is used as a switch that turns on or off a light automatically based on the recieved of intensity of light. By using the LDR components, it can design a series of light sensors for such items as outdoor light sensors, sleeping lights, garden lights, road lights that turn on at night and go out during the day automatically. The equipment used of the research were 2 test lamps, and done with 2 lighting sources, a natural source of lighting and an artificial source of lighting. From the research, it showed that the large light intensity affects the light flame by using LDR light sensor. It could be concluded that the greater of the light hitting intensity from the LDR surface was smaller than the value of the resistance and the flickering of the light. In contrast, the less light that affects the LDR, was the greater value of LDR resistance and lighter the light.